Probable drug–drug interaction between dabigatran and quinidine resulting in thrombin time rebound despite multiple idarucizumab doses. Issue 1 (January 2019) - George, Stephy; Taburyanskaya, Margarita; Lewis, Vicky
Abstract : N/A: Dabigatran is a direct thrombin inhibitor that was approved as an alternative to warfarin because it offers the benefit of predictable pharmacokinetic properties, favorable safety profile and ease of administration. Despite the improved safety profile, dabigatran use can lead to bleeding events. The bleeding risk associated with dabigatran is higher in the setting of renal impairment or drug–drug interactions resulting in supratherapeutic serum concentrations. Unfortunately, clinically significant interactions are not always identified by providers, especially in the case of infrequent drug–drug combinations. Dabigatran-related coagulopathy can be effectively reversed by idarucizumab. However, high dabigatran serum concentrations can lead to increased tissue distribution resulting in decreased idarucizumab efficacy and repeat idarucizumab doses may be warranted. This case describes a patient presenting with uncontrolled bleeding due to a significant drug–drug interaction between quinidine and dabigatran resulting in acute kidney injury and persistent coagulopathy despite multiple idarucizumab doses and transfusion measures.